2016
DOI: 10.3892/ol.2016.4317
|View full text |Cite
|
Sign up to set email alerts
|

Association between the methylation status of the MGMT promoter in bone marrow specimens and chemotherapy outcomes of patients with acute myeloid leukemia

Abstract: Abstract. The O(6)-methylguanine-DNA methyltransferase (MGMT)gene is a tumor suppressor gene that is associated with the risk of developing acute myeloid leukemia (AML). However, the association between the methylation status of the MGMT promoter and the chemotherapeutic outcomes of patients with AML remains unknown. In the present study, 30 bone marrow samples derived from patients with AML were collected prior and subsequent to chemotherapy. The methylation status of the MGMT promoter in the bone marrow spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…In contrast to t(8;21), we observed a reverse pattern of hypomethylation and higher expression of BASP1 in t(9;11) and other MLL rearranged AMLs. Other genes with hypomethylation and corresponding higher expression in t(8;21) vs. other subtypes included: MGMT (methylguanine-DNA methyltransferase), a tumor suppressor gene that has been associated with risk of AML development [ 38 ]; MPL (myeloproliferative leukemia virus oncogene), which has been shown to be essential for survival and self-renewal of human preleukemic t(8;21) cells [ 39 ]. Wildtype MPL has been shown to be overexpressed in t(8;21) AML and promote leukemia development via PI3K/AKT axis activation [ 40 ]; KDM4B , a histone specific demethylase, has been implicated in regulating expression of genes required for maintenance of hematopoiesis [ 41 ]; TCF3 , a fusion partner of PBX1 and 4-HLF in ALL [ 42 , 43 , 44 , 45 ], however its importance in AML is not currently known; and ABR that codes for an Active BCR related is involved in deactivation of RAC1 (ras-related C3 botulinum toxin substrate 1) important for hematopoiesis and leukemia [ 46 ]; we observed hypomethylation and low expression of ABR in t(8;21) ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to t(8;21), we observed a reverse pattern of hypomethylation and higher expression of BASP1 in t(9;11) and other MLL rearranged AMLs. Other genes with hypomethylation and corresponding higher expression in t(8;21) vs. other subtypes included: MGMT (methylguanine-DNA methyltransferase), a tumor suppressor gene that has been associated with risk of AML development [ 38 ]; MPL (myeloproliferative leukemia virus oncogene), which has been shown to be essential for survival and self-renewal of human preleukemic t(8;21) cells [ 39 ]. Wildtype MPL has been shown to be overexpressed in t(8;21) AML and promote leukemia development via PI3K/AKT axis activation [ 40 ]; KDM4B , a histone specific demethylase, has been implicated in regulating expression of genes required for maintenance of hematopoiesis [ 41 ]; TCF3 , a fusion partner of PBX1 and 4-HLF in ALL [ 42 , 43 , 44 , 45 ], however its importance in AML is not currently known; and ABR that codes for an Active BCR related is involved in deactivation of RAC1 (ras-related C3 botulinum toxin substrate 1) important for hematopoiesis and leukemia [ 46 ]; we observed hypomethylation and low expression of ABR in t(8;21) ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetic silencing of MGMT expression is frequently observed in several types of cancer as a consequence of transcriptional silencing induced by hypermethylation of the CpG island of the promoter of the MGMT gene [ 54 56 ]. Recent studies also indicate an association between the methylation status of the MGMT promoter and the development of MDS [ 57 ], adult AML [ 58 , 59 ] and childhood ALL [ 60 , 61 ]. In our study we found methylation of the MGMT promoter in 35.59% of patients with acute leukemia, but there was no significant difference in MGMT methylation status between AML and ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, chemotherapy-induced MGMT methylation status differed among various AML subtypes, gender and age of patients. Changes in MGMT methylation status were more frequent among M4 subtype patients (50%) and were not detected in M3 or M5 subtypes [ 58 ]. In several studies, methylation of the MGMT gene promoter has been associated with improved prognosis in young [ 62 ] and elderly [ 63 ] patients with newly diagnosed glioblastoma and in B-DLBCL patients [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The procedures of DNA extraction from peripheral blood and the subsequent bisulfite conversion were the same as previously described. [16] The BAX methylation was measured by qMSP, and the percentage of methylation ratios (PMRs) was applied to represent gene methylation levels. [17,18] The details of qMSP were available in our previous publications.…”
Section: Methodsmentioning
confidence: 99%